A Novel Mechanism for Cross-Adaptation between Heat and Altitude Acclimation: The Role of Heat Shock Protein 90. (12th May 2014) - Salgado, Roy M.; White, Ailish C.; Schneider, Suzanne M.; Mermier, Christine M.
Abstract : Heat shock protein 90 (HSP90) is a member of a family of molecular chaperone proteins which can be upregulated by various stressors including heat stress leading to increases in HSP90 protein expression. Its primary functions include (1) renaturing and denaturing of damaged proteins caused by heat stress and (2) interacting with client proteins to induce cell signaling for gene expression. The latter function is of interest because, in cancer cells, HSP90 has been reported to interact with the transcription hypoxic-inducible factor 1 α (HIF1 α ). In a normoxic environment, HIF1 α is degraded and therefore has limited physiological function. In contrast, in a hypoxic environment, stabilized HIF1 α acts to promote erythropoiesis and angiogenesis. Since HSP90 interacts with HIF1 α, and HSP90 can be upregulated from heat acclimation in humans, we present a proposal that heat acclimation can mimic molecular adaptations to those of altitude exposure. Specifically, we propose that heat acclimation increases HSP90 which then stabilizes HIF1 α in a normoxic environment. This has many implications since HIF1 α regulates red blood cell and vasculature formation. In this paper we will discuss (1) the functional roles of HSP90 and HIF1 α, (2) the interaction between HSP90 and other client proteins including HIF1 α, and (3) results from in vitro studies that may suggest how the relationship between HSP90 and HIF1 α might be applied to individuals preparing to make altitude sojourns.